A study of hearing improvement after myringoplasties in Bir Hospital, Kathmandu - Yadav, LK; Shrestha, D; Pradhananga, J (Journal of College of Medical Sciences-Nepal, 2012)
Myringoplasty is one of the most common ear surgery performed for chronic suppurative otitis media tubo tympanic type. The prime concern for patients who are willing to undergo myringoplasty is hearing improvement. The aim of this study is to assess the improvement of hearing after myringoplasties for Chronic Suppurative Otitis Media tubo tympanic type. The total number of patients included in the study was 105. Myringoplasties were performed in 129 patients, and only those who had graft uptake i.e. 105, were selected for the study. Age of the patients varied from 13 to 45 years. Pure tone audiogram was done before the operation and four weeks after the operation, and air conduction thresholds were compared. It was found that 83% of the patients had some degree of hearing improvement after the operation. No significant complications were observed except that few patients complained of pain at the site of incision for harvesting the graft. Thus, this study shows that, patients can be assured that the chances of hearing improvement is acceptable and can undergo the operation without fearing complications. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 31-35 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6723